IDENTIFIKASI JENIS KESULITAN MEMBACA PADA SISWA KELAS RENDAH SEKOLAH DASAR - Athas Jatipramono; Nur Amalia (Kwangsan: Jurnal Teknologi Pendidikan, 2022)
Reading is a fundamental ability for students to be able to follow learning at school. The ability to read is very necessary in learning in the classroom. But today there are still elementary school students who incidentally were already able to read the beginning, but in reality they are still not. It is feared that it will hinder the learning process in class. Based on the background of this problem, the researcher wanted to observe students with reading difficulties at the lower grade level at SDN Polokarto 01. Based on the teacher's report when the researcher attended the Teaching Campus program, the reason the researcher chose this location was because students were still found to have reading difficulties and the school was included in the 3t area. The purpose of this research is a. identified many students with reading difficulties at SDN Polokarto 01, b. knowing the factors that influence students having reading difficulties at SDN Polokarto 01, c. know the efforts to overcome reading difficulties in students at SDN Polokarto 01, and d. find out the teacher's difficulties in guiding students with reading difficulties. From the objectives above, the researcher will provide suggestions for solving the problem. The research method is descriptive qualitative with data collection through observation of students who have reading difficulties, interviews with class teachers and based on documentation of student assessment results. There were 9 students who had reading difficulties. The problems experienced by students are quite varied, students in grades 1, 2, 3. AbstrakMembaca merupakan kemampuan yang mendasar bagi peserta didik untuk dapat mengikuti pembelajaran di sekolah. Kemampuan membaca sangat diperlukan dalam pembelajaran di kelas. Namun dewasa ini masih ditemukan siswa Sekolah Dasar yang notabenenya sudah mampu membaca permulaan tetapi pada kenyataannya masih belum. Hal tersebut dikhawatirkan akan menghambat proses pembelajaran saat di kelas. Berdasarkan latar belakang permasalahan tersebut peneliti hendak mengamati siswa berkesulitan membaca jenjang kelas rendah di SDN Polokarto 01. Berdasarkan laporan guru saat peneliti mengikuti program Kampus Mengajar, alasan peneliti mengambil lokasi tersebut karena masih ditemukan siswa yang mengalami berkesulitan membaca dan sekolah termasuk daerah 3t. Adapun tujuan penelitian ini yaitu a. mengindentifikasi banyak siswa berkesulitan membaca di SDN Polokarto 01, b. mengetahui faktor yang mempengaruhi siswa mengalami berkesulitan membaca di SDN Polokarto 01, c. megetahui upaya untuk mengatasi berkesulitan membaca pada siswa di SDN Polokarto 01, dan d. mengetahui kesulitan guru dalam pembimbingan siswa berkesulitan membaca. Dari tujuan di atas peneliti akan memberikan saran pemecaham pada persoalan tersebut. Adapun metode penelitian yaitu kualitatif deskriptif dengan pengumpulan data melalui observasi siswa yang mengalami berkesulitan membaca, wawancara dengan guru kelas dan berdasarkan dokumentasi hasil penilaian siswa. Diperoleh 9 siswa yang mengalami berkesulitan membaca. Masalah yang dialami oleh siswa cukup bervariasi, siswa kelas 1, 2, 3.